Utilization Study of Nata De Soya from Soybean Wastewater As Adsorbent On Magnesium (Mg2+) and Calcium (Ca2+) Cations On Boiler Raw Water at PT. SMART Tbk - Chairuddin (Journal of Chemical Natural Resources, 2020)
The use of Nata De Soya prepared from soybean wastewater as an adsorbent on magnesium (Mg2+) and calcium(Ca2+) cations caused hard water in the boiler raw water at PT. SMART Tbk has been studied. Nata De Soya has been activated with H2SO4 1N before use as an adsorbent for Mg2+ and Ca2+ cations in the boiler raw water. The study resulted demonstrated that the optimum mass of adsorbent to adsorb Ca2+cation was 2.5 g with adsorption capacity at 60.64%. Meanwhile, the optimum mass of adsorbent to adsorb Mg2+cation was 2.0 g with the adsorption capacity at 66.34%. The regenerated Nata De Soya adsorbent has been also studied to adsorb Ca2+and Mg2+ cations. In other aspects, the percentage of Ca2+ and Mg2+ cations decrease by 9.27% and 9.47%, respectively after Nata De Soya treatment to the boiler raw water.